Surface-active permeability enhancer for increasing yield of low-permeability oil reservoir as well as preparation method and application of surface-active permeability enhancer

A surfactant permeability enhancer composed of betaine, nonionic surfactant, nano silicon dioxide, and graphene synergistically addresses low permeability and high consumption issues, achieving efficient oil recovery and production enhancement in low-permeability reservoirs.

CN119242283AActive Publication Date: 2025-01-03YANAN ZHONGSHIDA OIL & GAS ENG TECH SERVICE CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411256039.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-03
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Low-permeability unconventional reservoirs face challenges with low permeability enhancement and high surfactant consumption due to poor wettability and high oil-water interfacial tension, leading to inefficient oil recovery.

Method used

A surfactant permeability enhancer composed of betaine surfactant, nonionic surfactant, modified nano silicon dioxide, and graphene, synergistically reducing interfacial tension and enhancing adhesion to improve imbibition recovery.

Benefits of technology

The surfactant combination achieves over 30% spontaneous imbibition recovery at room temperature and over 55% at high temperature, with increased oil production by 30% in fracturing and reduced water content in ultra-low permeability reservoirs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034096190000131
    Figure BDA0005034096190000131
  • Figure BDA0005034096190000141
    Figure BDA0005034096190000141
Patent Text Reader

Abstract

The invention provides a surface active permeation enhancer for increasing the yield of a low-permeability oil reservoir as well as a preparation method and application of the surface active permeation enhancer. The surface active permeation enhancer comprises the following raw materials in parts by weight: 15-30 parts of a betaine type surfactant, 25-40 parts of a nonionic surfactant, 1-5 parts of modified nano silicon dioxide, 0.5-3 parts of graphene and 300-600 parts of water. According to the surface active permeability increasing agent for increasing the yield of the low-permeability oil reservoir, the imbibition recovery degree during spontaneous imbibition recovery of a rock core can be improved, and the oil connection antenna before and after imbibition is increased to about 120 degrees from about 33 degrees. When the permeability enhancer is used for tight reservoir volume fracturing, the average yield is increased by 30% or above compared with a conventional permeability enhancer stage. When being used for high-depth profile control and flooding of ultra-low permeability reservoirs, the water content in a stock solution is greatly reduced, and the oil yield is remarkably increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas development, and in particular to a surfactant permeability enhancer for increasing the production of low-permeability oil reservoirs, and a preparation method and application thereof. Background Art

[0002] Low-permeability unconventional reservoirs represented by tight oil and gas reservoirs have become an important area for oil and gas resource exploration and development in my country. The reservoir physical properties of this type of reservoir are poor, with a dense matrix, small reservoir pore throats, complex pore structure and poor connectivity, and low permeability. This type of reservoir is generally tested and put into production through large-scale volume fracturing. Under the dual medium conditions of dense matrix and complex fractures formed after fracturing, conventional injected water is easy to flow along the fracture system and is difficult to enter the reservoir matrix, resulting in a serious decline in the production of the corresponding oil wells.

[0003] Research on the imbibition mechanism in recent years has shown that the pore throats of low-permeability reservoirs are small and the capillary force is strong. Using imbibition to achieve oil and water replacement in fractures and matrix has become an important development mechanism for tight oil reservoirs, and it plays an important role in production-increasing measures such as fracturing, huff-and-puff, and water flooding. The wettability of the reservoir and the oil-water interfacial tension are key factors affecting the imbibition effect of low-permeability reservoirs. Since natural reservoirs generally show weak hydrophilicity and mixed wetting characteristics, and the oil-water interfacial tension is generally high, the efficiency of direct use of injection media for imbibition oil recovery is low, the degree of crude oil utilization in the matrix is ​​low, and the production-increasing benefits are low.

[0004] In the prior art, surfactants are often used as imbibing agents to reduce the oil-water interfacial tension, thereby reducing the deformation work of oil droplets passing through narrow pore throats and the resistance of oil droplets or oil films on the rock surface to be peeled off, thereby improving the recovery rate of oil and gas resources. However, in the actual production process, surfactants have the disadvantages of low imbibing and permeability enhancement capabilities, and the dosage and loss are high when used. Summary of the invention

[0005] The invention provides a surfactant permeability enhancer for increasing production in low permeability reservoirs, and a preparation method and application thereof, so as to solve the problems of low permeability and permeability enhancement ability and large consumption of surfactant in the prior art.

[0006] The invention provides a surfactant permeability enhancer for increasing the production of a low permeability oil reservoir. The surfactant permeability enhancer comprises the following raw materials in proportion by weight: 15-30 parts of a betaine surfactant, 25-40 parts of a nonionic surfactant, 1-5 parts of modified nano silicon dioxide, 0.5-3 parts of graphene and 300-600 parts of water.

[0007] Optionally, the surfactant penetration enhancer comprises raw materials in the following weight ratio: 20-25 parts of betaine surfactant, 30-35 parts of nonionic surfactant, 2-3 parts of modified nano-silicon dioxide, 1.5-2 parts of graphene, and 400-500 parts of water.

[0008] Optionally, the betaine-type surfactant is prepared by mixing cocamidopropyl betaine and perfluorohexylethylsulfonamidopropylethylcarboxy betaine in a mass ratio of (1-1.5):1.

[0009] Optionally, the nonionic surfactant is prepared by mixing a fluorocarbon chain nonionic surfactant and ethylenediamine oleate in a mass ratio of (2-3):1.

[0010] Optionally, the fluorocarbon chain nonionic surfactant is a double short fluorocarbon chain nonionic surfactant.

[0011] Optionally, the modification process of nano-silicon dioxide comprises the following steps:

[0012] S1: mixing ethanol and 3-mercaptopropyltriethoxysilane in a mass ratio of (4.5-5.5):1;

[0013] S2: Add nano-silicon dioxide in an amount of 1 / 120-1 / 110 of the mass of the mixed solution to the mixed solution obtained in S1, and stir and react at 25°C;

[0014] S3: centrifuging, washing, recrystallizing and drying the reaction product obtained in S2 in sequence to obtain an intermediate product after drying;

[0015] S4: dispersing the intermediate product obtained in S3 in dimethylformamide at a mass ratio of 1:(195-205), and performing ultrasonic dispersion;

[0016] S5: adding an oxygen-containing acid salt having the same mass as the intermediate product in S3 to the product obtained after ultrasonic dispersion in S4, and using a fluorinated surfactant as an initiator, reacting at 25° C. in an inert gas atmosphere;

[0017] S6: Transfer the product obtained in S5 into cyclohexane, collect and dry the precipitate to obtain modified nano-silica.

[0018] Optionally, the solvent used in the recrystallization in S3 is acetonitrile. The oxygen-containing acid salt used in S5 is sodium oleate, and the fluorine surfactant is sodium perfluorononenyloxybenzenesulfonate. The inert gas is one of nitrogen and helium.

[0019] Optionally, during the stirring reaction in S2, the stirring speed is 500-600 r / min, and the stirring time is 25-30 min. The ultrasonic dispersion time in S4 is 25-30 min, the dispersion power is 1000-1100 W, and the dispersion frequency is 20-25 KHz.

[0020] The present invention also provides a method for preparing a surfactant permeability enhancer for increasing production in low permeability oil reservoirs, comprising the following steps:

[0021] Weigh the following raw materials by weight: 15-30 parts of betaine surfactant, 25-40 parts of nonionic surfactant, 1-5 parts of modified nano-silicon dioxide, 0.5-3 parts of graphene, and 300-600 parts of water;

[0022] The betaine type surfactant, the nonionic surfactant and 90% of water are uniformly mixed to prepare a surfactant base liquid;

[0023] The modified nano-silicon dioxide is mixed evenly with the remaining 10% of water to prepare a silicon dioxide base liquid;

[0024] Graphene and silicon dioxide base liquid are added into a surfactant base liquid under the conditions of ultrasonic dispersion and mechanical stirring to obtain a surfactant penetration enhancer.

[0025] The present invention also provides an application of a surfactant permeability enhancer for increasing the production of a low permeability oil reservoir. The surfactant permeability enhancer is used as a chemical agent in the production process of a low permeability oil reservoir.

[0026] The beneficial effects of the surfactant for increasing the production of low permeability reservoirs provided by the present invention include: 1. When used for spontaneous imbibition recovery of cores, the normal temperature imbibition recovery degree (total recovery rate) can reach more than 30%, and the high temperature imbibition recovery degree (total recovery rate) can reach more than 55%.

[0027] 2. The contact angle of the oil phase increased from about 33° to about 120° before and after imbibition.

[0028] 3. When used for volume fracturing of tight oil reservoirs, the average production increases by more than 30% compared with the conventional permeability enhancer stage.

[0029] 4. When used for deep displacement of ultra-low permeability oil reservoirs, the water content in the original fluid is greatly reduced and the oil production is significantly increased. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present invention.

[0031] The invention provides a surfactant permeability enhancer for increasing the production of a low permeability oil reservoir. The surfactant permeability enhancer comprises the following raw materials in proportion by weight: 15-30 parts of a betaine surfactant, 25-40 parts of a nonionic surfactant, 1-5 parts of modified nano silicon dioxide, 0.5-3 parts of graphene and 300-600 parts of water.

[0032] The surfactant penetration enhancer includes betaine-type surfactant, nonionic surfactant, modified nano-silica, graphene and water. Among them, modified nano-silica can enhance the adhesion to the exposed surface of the rock, thereby generating a strong structural separation pressure in the wedge-shaped area of ​​the oil film to erode the oil film and enhance the hydrophilicity of the reservoir. Betaine-type surfactant and nonionic surfactant can adjust the oil-water interfacial tension, solubilize and disperse the detached oil film, reduce the size of oil droplets, and enhance the ability of oil absorption and drainage. Graphene is selected as graphene oxide, which can change the wettability of the rock and reduce the interfacial tension.

[0033] Although single nano-silicon dioxide, surfactant or graphene oxide have certain effects on improving the recovery rate when used for the exploitation of low permeability oil reservoirs, the effect is not as good as the system of the three compounded. The surfactant permeability enhancer provided in the present invention is compounded with nano-silicon dioxide, surfactant and graphene oxide so that the three act synergistically, which not only improves the efficiency of the low permeability oil reservoir recovery but also reduces the dosage of the permeability enhancer under the same conditions.

[0034] Graphene oxide can effectively reduce the oil-water interfacial tension and change the wettability of rocks. When graphene oxide is compounded with surfactants, the synergistic effect of the two not only accelerates the rate of imbibition, but also increases the final imbibition recovery of the core. Modified nano-silica is compounded with surfactants. Modified nano-silica can increase the hydrophilicity of the core surface through adsorption on the core surface and the "wedge separation pressure" effect. The synergistic effect of the two can effectively improve the degree of imbibition recovery. At the same time, the hydrophilic group of the surfactant can be combined with the surface of the modified nano-silica particles, so that the hydrophobic chain of the surfactant is exposed on the surface of the modified nano-silica particles, thereby making the surface of the modified nano-silica particles partially hydrophobic, which helps to reduce the interfacial tension.

[0035] Furthermore, the surfactant penetration enhancer comprises the following raw materials in the following weight proportions: 20-25 parts of betaine surfactant, 30-35 parts of nonionic surfactant, 2-3 parts of modified nano-silicon dioxide, 1.5-2 parts of graphene, and 400-500 parts of water.

[0036] Further, the betaine surfactant is formed by mixing cocamidopropyl betaine and perfluorohexylethylsulfonamidopropylethylcarboxy betaine in a mass ratio of (1-1.5): 1. Further, the nonionic surfactant is formed by mixing a fluorocarbon chain nonionic surfactant and ethylenediamine oleate in a mass ratio of (2-3): 1. Further, the fluorocarbon chain nonionic surfactant is a double short fluorocarbon chain nonionic surfactant.

[0037] Compound surfactants are of great significance to achieving cost reduction and efficiency improvement. Compounding multiple surfactants can not only play a synergistic role, but also achieve cost reduction and efficiency improvement, and at the same time can significantly improve the effect of imbibition and increase the recovery rate of oil and gas.

[0038] Fluorocarbon surfactants have the outstanding characteristics of "three highs and two hates", namely high chemical stability, high surface activity, high heat resistance, and hydrophobicity and oleophobicity. Although fluorocarbon surfactants can stably exist and be used in strong acid, strong alkali, strong oxidation and even high temperature systems, due to their hydrophobicity and oleophobicity, they have poor affinity with water and oil, resulting in generally high interfacial tension, which is not conducive to direct use on the interface. In order to give full play to the characteristics of fluorocarbon surfactants and improve the performance of conventional surfactants, fluorocarbon surfactants are used in combination with conventional surfactants (hydrocarbon surfactants).

[0039] Compared with hydrocarbon surfactants, the molecules of perfluorohexyl ethyl sulfonamidopropyl ethyl carboxy betaine are more easily entangled with each other to form micelles. Perfluorohexyl ethyl sulfonamidopropyl ethyl carboxy betaine, double short fluorocarbon chain nonionic surfactant and cocoamidopropyl betaine cooperate with each other, so that synergistic adsorption can occur on the interface. The single surfactant system has a stronger ability to reduce interfacial tension, thereby better meeting the spreading conditions.

[0040] When exploiting oil reservoirs, ionic surfactants and amphoteric surfactants have higher interfacial effectiveness at the oil-water interface, while non-ionic surfactants have higher interfacial density. Amphoteric surfactants perfluorohexyl ethylsulfonamidopropyl ethylcarboxy betaine, cocamidopropyl betaine, nonionic surfactants double short fluorocarbon chain nonionic surfactants, and ethylenediamine oleate are mixed. The multi-component system after mixing will form a mixed adsorption layer at the oil-water interface, and because the hydrocarbon chain and the fluorocarbon chain are mutually repellent, the arrangement of molecules on the adsorption layer at the oil-water interface will present a bilayer structure. The fluorocarbon chains are tightly arranged in the upper layer, and the hydrocarbon chains are cross-arranged under the fluorocarbon chains. The non-ionic hydrophilic groups face the water end, and the dense hydrocarbon chain adsorption layer formed at the interface is on the oil end, thereby significantly reducing the oil-water interfacial tension. In addition, the fluorocarbon bond is more stable than the carbon-hydrogen bond, so the presence of the carbon-fluorine bond improves the stability of the multi-compound system. In addition, there are hydrophilic head groups connected by chemical bonds in the molecules of amphoteric fluorinated surfactants. Under the action of chemical bonds, the repulsion between the hydrophilic head groups is greatly weakened, which in turn enables the molecules to be arranged more closely on the surface of the medium, thereby further reducing the surface tension of the oil-water interface. Ethylenediamine oleate is also a non-ionic surfactant, which has good compatibility with other surfactants, strong wetting, penetration and dissolving power, and long lasting effect.

[0041] In addition, there is almost no electrostatic repulsion between the hydrophilic groups of non-ionic surfactant molecules in the multicomponent system, which makes the surfactant molecules more closely arranged at the oil-water interface, thereby lowering the surface tension.

[0042] Preferably, the preparation process of the double short fluorocarbon chain nonionic surfactant is as follows:

[0043] 1) 1H, 1H, 2H, 2H-perfluorohexan-1-ol and isophorone diisocyanate are mixed uniformly in a molar ratio of 1:1, and the mixture is heated to 80° C.;

[0044] 2) Add bismuth neodecanoate to the heated reaction solution and react at a constant temperature for 5 hours.

[0045] 3) Continue to add excess polyethylene glycol to the reaction solution and continue the reaction at a constant temperature for 7 hours.

[0046] 4) Filter the crude product, dialyze the filtered product in deionized water for 12 hours, and freeze-dry the purified product to obtain a double short fluorocarbon chain nonionic surfactant.

[0047] The polyethylene glycol hydrophilic chain in the molecular structure of the double short fluorocarbon chain nonionic surfactant connects the two short fluorocarbon chains together, making the arrangement of the fluorocarbon chains at the oil-water interface more compact, thereby effectively reducing the surface tension. In addition, both perfluorohexylethylsulfonamidopropylethylcarboxybetaine and double short fluorocarbon chain nonionic surfactants have fewer fluorinated carbon atoms, less environmental pollution, and are not prohibited or restricted organic pollutants in the Stockholm Convention.

[0048] Further, the modification process of nano-silicon dioxide includes the following steps:

[0049] S1: mixing ethanol and 3-mercaptopropyltriethoxysilane in a mass ratio of (4.5-5.5):1;

[0050] S2: Add nano-silicon dioxide in an amount of 1 / 120-1 / 110 of the mass of the mixed solution to the mixed solution obtained in S1, and stir and react at 25°C;

[0051] S3: centrifuging, washing, recrystallizing and drying the reaction product obtained in S2 in sequence to obtain an intermediate product after drying;

[0052] S4: dispersing the intermediate product obtained in S3 in dimethylformamide at a mass ratio of 1:(195-205), and performing ultrasonic dispersion;

[0053] S5: adding an oxygen-containing acid salt having the same mass as the intermediate product in S3 to the product obtained after ultrasonic dispersion in S4, and using a fluorinated surfactant as an initiator, reacting at 25° C. in an inert gas atmosphere;

[0054] S6: Transfer the product obtained in S5 into cyclohexane, collect and dry the precipitate to obtain modified nano-silica.

[0055] Furthermore, the solvent used in the recrystallization in S3 is acetonitrile. The oxygen-containing acid salt used in S5 is sodium oleate, and the fluorine surfactant is sodium perfluorononenyloxybenzenesulfonate. The inert gas is one of nitrogen and helium.

[0056] Furthermore, when the stirring reaction is carried out in S2, the stirring speed is 500-600 r / min, and the stirring time is 25-30 min. The ultrasonic dispersion time in S4 is 25-30 min, the dispersion power is 1000-1100 W, and the dispersion frequency is 20-25 KHz.

[0057] Furthermore, the preparation method of the surfactant permeability enhancer for increasing the production of low permeability reservoirs is as follows:

[0058] Weigh the following raw materials by weight: 15-30 parts of betaine surfactant, 25-40 parts of nonionic surfactant, 1-5 parts of modified nano-silicon dioxide, 0.5-3 parts of graphene, and 300-600 parts of water;

[0059] The betaine type surfactant, the nonionic surfactant and 90% of water are uniformly mixed to prepare a surfactant base liquid;

[0060] The modified nano-silicon dioxide is mixed evenly with the remaining 10% of water to prepare a silicon dioxide base liquid;

[0061] Graphene and silicon dioxide base liquid are added into a surfactant base liquid under the conditions of ultrasonic dispersion and mechanical stirring to obtain a surfactant penetration enhancer.

[0062] Furthermore, the surfactant permeability enhancer for increasing the production of low permeability oil reservoirs is used as a chemical agent in the production process of low permeability oil reservoirs.

[0063] The present invention is further described in detail below in conjunction with specific embodiments.

[0064] Example 1

[0065] A surfactant permeability enhancer for increasing the production of low permeability reservoirs comprises the following raw materials in weight proportion: 15 parts of betaine surfactant, 25 parts of nonionic surfactant, 1 part of modified nano-silicon dioxide, 0.5 parts of graphene, and 300 parts of water. The betaine surfactant comprises 7.5 parts of cocamidopropyl betaine and 7.5 parts of perfluorohexylethylsulfonamidopropylethylcarboxylic betaine, with a ratio of 1:1. The nonionic surfactant comprises 16.7 parts of double short fluorocarbon chain nonionic surfactant and 8.3 parts of ethylenediamine oleate, with a ratio of 2:1.

[0066] Among them, the preparation process of the double short fluorocarbon chain nonionic surfactant is as follows:

[0067] 1) 1H, 1H, 2H, 2H-perfluorohexan-1-ol and isophorone diisocyanate are mixed uniformly in a molar ratio of 1:1, and the mixture is heated to 80° C.;

[0068] 2) Add bismuth neodecanoate to the heated reaction solution and react at a constant temperature for 5 hours.

[0069] 3) Continue to add excess polyethylene glycol to the reaction solution and continue the reaction at a constant temperature for 7 hours.

[0070] 4) Filter the crude product, dialyze the filtered product in deionized water for 12 hours, and freeze-dry the purified product to obtain a double short fluorocarbon chain nonionic surfactant.

[0071] The modification process of modified nano-silica includes the following steps:

[0072] S1: mixing ethanol and 3-mercaptopropyltriethoxysilane in a mass ratio of 4.5:1;

[0073] S2: Add nano-silicon dioxide in an amount of 1 / 120 of the mass of the mixed solution to the mixed solution obtained in S1, and stir the mixture at 25°C and 500 r / min for 25 min;

[0074] S3: the reaction product obtained in S2 is centrifuged, washed, recrystallized in acetonitrile and then dried to obtain an intermediate product;

[0075] S4: Disperse the intermediate product obtained in S3 in dimethylformamide at a mass ratio of 1:195, and disperse it ultrasonically at 1000W and 20KHz for 20min;

[0076] S5: adding sodium oleate having the same mass as the intermediate product in S3 to the product obtained after ultrasonic dispersion in S4, and using sodium perfluorononenyloxybenzenesulfonate as an initiator, reacting at 25° C. under a nitrogen atmosphere;

[0077] S6: Transfer the product obtained in S5 into cyclohexane, collect and dry the precipitate to obtain modified nano-silica.

[0078] A method for preparing a surfactant penetration enhancer comprises the following steps:

[0079] 1) After the raw materials are weighed and prepared, the betaine surfactant, the nonionic surfactant and 90% of water are evenly mixed to prepare a surfactant base liquid;

[0080] 2) uniformly mixing the modified nano-silicon dioxide with the remaining 10% of water to prepare a silicon dioxide base liquid;

[0081] 3) adding graphene and silica base liquid to the surfactant base liquid under the conditions of ultrasonic dispersion and mechanical stirring to obtain a surfactant penetration enhancer.

[0082] The prepared surfactant permeability enhancer was used in the spontaneous imbibition experiment, and the spontaneous imbibition recovery degree of the core and the oil phase contact angle before and after spontaneous imbibition were measured.

[0083] Example 2

[0084] The raw material weight, proportion and preparation process parameters of the surfactant permeability enhancer are exactly the same as those in Example 1. The surfactant permeability enhancer is used for volume fracturing of tight oil reservoirs, and its effect of volume fracturing of tight oil reservoirs is recorded.

[0085] Example 3

[0086] The raw material weight, proportion and preparation process parameters of the surfactant permeability enhancer are exactly the same as those in Example 1. The surfactant permeability enhancer is used for high-depth flooding of ultra-low permeability reservoirs, and its flooding effect is recorded.

[0087] Example 4

[0088] A surfactant permeability enhancer for increasing the production of low permeability reservoirs comprises the following raw materials in weight proportion: 30 parts of betaine surfactant, 40 parts of nonionic surfactant, 5 parts of modified nano-silicon dioxide, 3 parts of graphene, and 600 parts of water. Among the betaine surfactant, 18 parts of cocamidopropyl betaine and 12 parts of perfluorohexylethylsulfonamidopropylethylcarboxylic betaine are contained in a ratio of 1.5:1. Among the nonionic surfactant, 30 parts of double short fluorocarbon chain nonionic surfactant and 10 parts of ethylenediamine oleate are contained in a ratio of 3:1.

[0089] Among them, the preparation process of the double short fluorocarbon chain nonionic surfactant is as follows:

[0090] 1) 1H, 1H, 2H, 2H-perfluorohexan-1-ol and isophorone diisocyanate are mixed uniformly in a molar ratio of 1:1, and the mixture is heated to 80° C.;

[0091] 2) Add bismuth neodecanoate to the heated reaction solution and react at a constant temperature for 5 hours.

[0092] 3) Continue to add excess polyethylene glycol to the reaction solution and continue the reaction at a constant temperature for 7 hours.

[0093] 4) Filter the crude product, dialyze the filtered product in deionized water for 12 hours, and freeze-dry the purified product to obtain a double short fluorocarbon chain nonionic surfactant.

[0094] The modification process of modified nano-silica includes the following steps:

[0095] S1: mixing ethanol and 3-mercaptopropyltriethoxysilane in a mass ratio of 5.5:1;

[0096] S2: Add 1 / 110 the mass of nano-silicon dioxide to the mixed solution obtained in S1, and stir at 25°C and 600 r / min for 30 min;

[0097] S3: the reaction product obtained in S2 is centrifuged, washed, recrystallized in acetonitrile and then dried to obtain an intermediate product;

[0098] S4: The intermediate product obtained in S3 is dispersed in dimethylformamide at a mass ratio of 1:205, and ultrasonically dispersed at 1100W and 25KHz for 30min;

[0099] S5: adding sodium oleate having the same mass as the intermediate product in S3 to the product obtained after ultrasonic dispersion in S4, and using sodium perfluorononenyloxybenzenesulfonate as an initiator, reacting at 25° C. in a helium atmosphere;

[0100] S6: Transfer the product obtained in S5 into cyclohexane, collect and dry the precipitate to obtain modified nano-silica.

[0101] A method for preparing a surfactant penetration enhancer comprises the following steps:

[0102] 1) After the raw materials are weighed and prepared, the betaine surfactant, the nonionic surfactant and 90% of water are evenly mixed to prepare a surfactant base liquid;

[0103] 2) uniformly mixing the modified nano-silicon dioxide with the remaining 10% of water to prepare a silicon dioxide base liquid;

[0104] 3) adding graphene and silica base liquid to the surfactant base liquid under the conditions of ultrasonic dispersion and mechanical stirring to obtain a surfactant penetration enhancer.

[0105] The prepared surfactant permeability enhancer was used in the spontaneous imbibition experiment, and the spontaneous imbibition recovery degree of the core and the oil phase contact angle before and after spontaneous imbibition were measured.

[0106] Example 5

[0107] The raw material weight, proportion and preparation process parameters of the surfactant permeability enhancer are exactly the same as those in Example 4. The surfactant permeability enhancer is used for volume fracturing of tight oil reservoirs, and its effect of volume fracturing of tight oil reservoirs is recorded.

[0108] Example 6

[0109] The raw material weight, proportion and preparation process parameters of the surfactant permeability enhancer are exactly the same as those in Example 4. The surfactant permeability enhancer is used for high-depth flooding of ultra-low permeability reservoirs, and its flooding effect is recorded.

[0110] Example 7

[0111] A surfactant permeability enhancer for increasing the production of low permeability reservoirs comprises the following raw materials in weight proportion: 23 parts of betaine surfactant, 35 parts of nonionic surfactant, 2.5 parts of modified nano-silicon dioxide, 1.8 parts of graphene, and 450 parts of water. Among the betaine surfactant, 13 parts of cocamidopropyl betaine and 10 parts of perfluorohexylethylsulfonamidopropylethylcarboxylic betaine are included in the ratio of 1.3:1. Among the nonionic surfactant, 25 parts of double short fluorocarbon chain nonionic surfactant and 10 parts of ethylenediamine oleate are included in the ratio of 2.5:1.

[0112] Among them, the preparation process of the double short fluorocarbon chain nonionic surfactant is as follows:

[0113] 1) 1H, 1H, 2H, 2H-perfluorohexan-1-ol and isophorone diisocyanate are mixed uniformly in a molar ratio of 1:1, and the mixture is heated to 80° C.;

[0114] 2) Add bismuth neodecanoate to the heated reaction solution and react at a constant temperature for 5 hours.

[0115] 3) Continue to add excess polyethylene glycol to the reaction solution and continue the reaction at a constant temperature for 7 hours.

[0116] 4) Filter the crude product, dialyze the filtered product in deionized water for 12 hours, and freeze-dry the purified product to obtain a double short fluorocarbon chain nonionic surfactant.

[0117] The modification process of modified nano-silica includes the following steps:

[0118] S1: mixing ethanol and 3-mercaptopropyltriethoxysilane in a mass ratio of 5:1;

[0119] S2: Add nano-silicon dioxide in an amount of 1 / 115 of the mass of the mixed solution to the mixed solution obtained in S1, and stir the mixture at 25°C and 550 r / min for 27 min;

[0120] S3: the reaction product obtained in S2 is centrifuged, washed, recrystallized in acetonitrile and then dried to obtain an intermediate product;

[0121] S4: The intermediate product obtained in S3 was dispersed in dimethylformamide at a mass ratio of 1:200, and ultrasonically dispersed at 1050W and 23KHz for 27min;

[0122] S5: adding sodium oleate having the same mass as the intermediate product in S3 to the product obtained after ultrasonic dispersion in S4, and using sodium perfluorononenyloxybenzenesulfonate as an initiator, reacting at 25° C. under a nitrogen atmosphere;

[0123] S6: Transfer the product obtained in S5 into cyclohexane, collect and dry the precipitate to obtain modified nano-silica.

[0124] A method for preparing a surfactant penetration enhancer comprises the following steps:

[0125] 1) After the raw materials are weighed and prepared, the betaine surfactant, the nonionic surfactant and 90% of water are evenly mixed to prepare a surfactant base liquid;

[0126] 2) uniformly mixing the modified nano-silicon dioxide with the remaining 10% of water to prepare a silicon dioxide base liquid;

[0127] 3) adding graphene and silica base liquid to the surfactant base liquid under the conditions of ultrasonic dispersion and mechanical stirring to obtain a surfactant penetration enhancer.

[0128] The prepared surfactant permeability enhancer was used in the spontaneous imbibition experiment, and the spontaneous imbibition recovery degree of the core and the oil phase contact angle before and after spontaneous imbibition were measured.

[0129] Example 8

[0130] The raw material weight, proportion and preparation process parameters of the surfactant permeability enhancer are exactly the same as those in Example 7. The surfactant permeability enhancer is used for volume fracturing of tight oil reservoirs, and its effect of volume fracturing of tight oil reservoirs is recorded.

[0131] Example 9

[0132] The raw material weight, proportion and preparation process parameters of the surfactant permeability enhancer are exactly the same as those in Example 7. The surfactant permeability enhancer is used for high-depth flooding of ultra-low permeability reservoirs, and its flooding effect is recorded.

[0133] Example 10

[0134] A surfactant permeability enhancer for increasing the production of low permeability reservoirs comprises the following raw materials in weight proportion: 15 parts of betaine surfactant, 40 parts of nonionic surfactant, 5 parts of modified nano-silicon dioxide, 0.5 parts of graphene, and 600 parts of water. Among the betaine surfactant, 9 parts of cocamidopropyl betaine and 6 parts of perfluorohexylethylsulfonamidopropylethylcarboxylic betaine are contained in a ratio of 1.5:1. Among the nonionic surfactant, 26.7 parts of double short fluorocarbon chain nonionic surfactant and 13.3 parts of ethylenediamine oleate are contained in a ratio of 2:1.

[0135] Among them, the preparation process of the double short fluorocarbon chain nonionic surfactant is as follows:

[0136] 1) 1H, 1H, 2H, 2H-perfluorohexan-1-ol and isophorone diisocyanate are mixed uniformly in a molar ratio of 1:1, and the mixture is heated to 80° C.;

[0137] 2) Add bismuth neodecanoate to the heated reaction solution and react at a constant temperature for 5 hours.

[0138] 3) Continue to add excess polyethylene glycol to the reaction solution and continue the reaction at a constant temperature for 7 hours.

[0139] 4) Filter the crude product, dialyze the filtered product in deionized water for 12 hours, and freeze-dry the purified product to obtain a double short fluorocarbon chain nonionic surfactant.

[0140] The modification process of modified nano-silica includes the following steps:

[0141] S1: mixing ethanol and 3-mercaptopropyltriethoxysilane in a mass ratio of 4.5:1;

[0142] S2: Add nano-silicon dioxide in an amount of 1 / 115 of the mass of the mixed solution to the mixed solution obtained in S1, and stir the mixture at 25°C and 500 r / min for 30 min;

[0143] S3: the reaction product obtained in S2 is centrifuged, washed, recrystallized in acetonitrile and then dried to obtain an intermediate product;

[0144] S4: The intermediate product obtained in S3 is dispersed in dimethylformamide at a mass ratio of 1:195, and ultrasonically dispersed at 1100W and 20KHz for 25min;

[0145] S5: adding sodium oleate having the same mass as the intermediate product in S3 to the product obtained after ultrasonic dispersion in S4, and using sodium perfluorononenyloxybenzenesulfonate as an initiator, reacting at 25° C. in a helium atmosphere;

[0146] S6: Transfer the product obtained in S5 into cyclohexane, collect and dry the precipitate to obtain modified nano-silica.

[0147] A method for preparing a surfactant penetration enhancer comprises the following steps:

[0148] 1) After the raw materials are weighed and prepared, the betaine surfactant, the nonionic surfactant and 90% of water are evenly mixed to prepare a surfactant base liquid;

[0149] 2) uniformly mixing the modified nano-silicon dioxide with the remaining 10% of water to prepare a silicon dioxide base liquid;

[0150] 3) adding graphene and silica base liquid to the surfactant base liquid under the conditions of ultrasonic dispersion and mechanical stirring to obtain a surfactant penetration enhancer.

[0151] The prepared surfactant permeability enhancer was used in the spontaneous imbibition experiment, and the spontaneous imbibition recovery degree of the core and the oil phase contact angle before and after spontaneous imbibition were measured.

[0152] Embodiment 11

[0153] The surfactant permeability enhancer raw material weight, ratio and preparation process parameters are exactly the same as those in Example 10. The surfactant permeability enhancer is used for volume fracturing of tight oil reservoirs, and its effect on volume fracturing of tight oil reservoirs is recorded.

[0154] Example 12

[0155] The raw material weight, proportion and preparation process parameters of the surfactant permeability enhancer are exactly the same as those in Example 10. The surfactant permeability enhancer is used for high-depth flooding of ultra-low permeability reservoirs, and its flooding effect is recorded.

[0156] The experimental results of spontaneous imbibition recovery degree of the cores and the oil phase contact angle before and after spontaneous imbibition of Example 1, Example 4, Example 7 and Example 10 are shown in Table 1:

[0157] Table 1

[0158] Example 1 Example 4 Example 7 Example 10 Small hole recovery rate (25℃) 41% 53% 45% 46% Small hole recovery rate (65℃) 50% 59% 53% 54% Macropore recovery rate (25℃) 19% 30% 24% 26% Macropore recovery rate (65℃) 70% 79% 74% 75% Total recovery rate (25℃) 30% 43% 35% 37% Total recovery rate (65℃) 55% 67% 62% 60% Oil phase contact angle before imbibition 31.2° 33.2° 37.2° 34.3° Oil phase contact angle after imbibition 118.9° 131.5° 125.2° 121.7°

[0159] It can be seen from the data of Examples 1, 4, 7 and 10 and Table 1 that when the surfactant permeability enhancer for increasing the production of low permeability oil reservoirs provided by the present invention is used for spontaneous imbibition recovery of cores, the degree of imbibition recovery at room temperature (total recovery rate) can reach more than 30%, and the degree of imbibition recovery at high temperature (total recovery rate) can reach more than 55%. The oil phase contact angle before and after imbibition increases from about 33° to about 120°.

[0160] The experimental results of Example 2, Example 5, Example 8 and Example 11 for volume fracturing of tight oil reservoirs are shown in Table 2:

[0161] Table 2

[0162]

[0163]

[0164] It can be seen from the data of Examples 2, 5, 8 and 11 and Table 1 that when the surfactant permeability enhancer for increasing production in low permeability reservoirs provided by the present invention is used for volume fracturing of tight reservoirs, the production of multiple test wells is more than 2700t after 6 months of production. Compared with the average stage production of the control wells without the surfactant permeability enhancer, the stage production is increased by more than 30% (the total stage production of the 6-month stage of the three blank test wells used in the experiment is 2154t, 2191t, and 1591t respectively).

[0165] The examples 3, 6, 9 and 12 are used for regulating and flooding in deep parts of ultra-low permeability reservoirs, and the regulating and flooding effects are recorded in Table 3:

[0166] Table 3

[0167] Example 3 Example 6 Example 9 Example 12 <![CDATA[Nissan liquid (m 3 )]]> 15.7 17.1 16.1 16.5 Moisture content (%) 45 37 39 42 <![CDATA[Daily oil production (m 3 )]]> 8.6 10.7 9.8 9.6 Dynamic liquid level(m) 1570 1630 1580 1600

[0168] It can be seen from the data of Examples 3, 6, 9 and 12 and Table 1 that when the surfactant permeability enhancer for increasing production in low permeability reservoirs provided by the present invention is used for high-depth flooding of ultra-low permeability reservoirs, the water content in the stock solution is greatly reduced and the oil production is significantly increased (in the blank experiment, the average daily liquid production is 35.7m 3 , water content is 100%, daily oil production is 0, and the dynamic liquid level is below 950m).

[0169] Comparative Example 1

[0170] The only difference between Comparative Example 1 and Example 7 is that no nonionic surfactant is added.

[0171] Comparative Example 2

[0172] The only difference between Comparative Example 2 and Example 7 is that no perfluorohexylethylsulfonamidopropylethylcarboxybetaine is added to the betaine-type surfactant.

[0173] Comparative Example 3

[0174] The only difference between Comparative Example 3 and Example 7 is that no graphene is added.

[0175] The experimental results of spontaneous imbibition recovery degree of the cores of Comparative Examples 1-3 and the oil phase contact angle before and after spontaneous imbibition are shown in Table 4

[0176] Table 4

[0177] Comparative Example 1 Comparative Example 2 Comparative Example 3 Small hole recovery rate (25℃) 26% 33% 36% Small hole recovery rate (65℃) 34% 42% 45% Macropore recovery rate (25℃) 11% 17% 19% Macropore recovery rate (65℃) 41% 59% 65% Total recovery rate (25℃) 15% 27% 31% Total recovery rate (65℃) 32% 48% 52% Oil phase contact angle before imbibition 36.7° 37.3° 37.6° Oil phase contact angle after imbibition 105.2° 109.7° 114.2°

[0178] Comparative Example 4

[0179] The only difference between Comparative Example 4 and Example 8 is that no nonionic surfactant is added.

[0180] Comparative Example 5

[0181] The only difference between Comparative Example 5 and Example 8 is that no perfluorohexylethylsulfonamidopropylethylcarboxybetaine is added to the betaine-type surfactant.

[0182] Comparative Example 6

[0183] The only difference between Comparative Example 6 and Example 8 is that no graphene is added.

[0184] The experimental results of Comparative Examples 4-6 for volume fracturing of tight oil reservoirs are shown in Table 5:

[0185] Table 5:

[0186] Comparative Example 4 Comparative Example 5 Comparative Example 6 Production of the test well in the first month of production 381t 398t 405t Production of the test well in the second month of production 396t 404t 401t Production of the test well in the third month of production 402t 410t 409t Production of the test well in the fourth month of production 411t 416t 414t Production of the test well in the fifth month of production 417t 401t 407t Production of the test well in the sixth month of production 410t 405t 412t Total production of test wells 2401t 2434t 2448t

[0187] Comparative Example 7

[0188] The only difference between Comparative Example 7 and Example 9 is that no nonionic surfactant is added.

[0189] Comparative Example 8

[0190] The only difference between Comparative Example 8 and Example 9 is that no perfluorohexylethylsulfonamidopropylethylcarboxybetaine is added to the betaine-type surfactant.

[0191] Comparative Example 9

[0192] The only difference between Comparative Example 9 and Example 9 is that no graphene is added.

[0193] The experimental results of Comparative Examples 7-9 for volume fracturing of tight oil reservoirs are shown in Table 6:

[0194] Table 6

[0195] Comparative Example 7 Comparative Example 8 Comparative Example 9 <![CDATA[Nissan liquid (m 3 )]]> 14.7 16.2 15.5 Moisture content (%) 62 67 49 <![CDATA[Daily oil production (m 3 )]]> 5.6 5.3 7.6 Dynamic liquid level(m) 1560 1660 1570

[0196] It can be seen from the experimental data of Comparative Examples 1-9 and Tables 4-6 that when no nonionic surfactant is added, all indicators of the surfactant penetration enhancer used for increasing the production of low permeability reservoirs are greatly reduced. On the one hand, the reason is that after the nonionic surfactant is lost, the remaining betaine surfactant is an amphoteric surfactant, and there is a certain electrostatic repulsion between the amphoteric surfactants, so that the surfactant molecules are not arranged as tightly as before, and the effect of reducing the surface tension is poor. On the other hand, after the double short fluorocarbon chain nonionic surfactant is lost, there is no connection effect of polyethylene glycol, which makes the surfactant at the oil-water interface loosely arranged.

[0197] When perfluorohexylethylsulfonamidopropylethylcarboxybetaine is not added, the synergistic adsorption effect of the surfactant penetration enhancer at the oil-water interface decreases, which in turn reduces the yield-increasing effect.

[0198] The effect of graphene oxide on increasing oil reservoir production is relatively small, but compared with the amount added and the effect of increasing production, it still achieves the result of reducing costs and increasing efficiency.

[0199] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A surfactant permeability enhancer for increasing the production of low permeability oil reservoirs, characterized in that: The surfactant penetration enhancer comprises the following raw materials in the following weight proportions: 15-30 parts of betaine surfactant, 25-40 parts of nonionic surfactant, 1-5 parts of modified nano silicon dioxide, 0.5-3 parts of graphene and 300-600 parts of water.

2. The surfactant for increasing the production of low permeability reservoirs according to claim 1, characterized in that: The surfactant penetration enhancer comprises the following raw materials in the following weight proportions: 20-25 parts of betaine surfactant, 30-35 parts of nonionic surfactant, 2-3 parts of modified nano silicon dioxide, 1.5-2 parts of graphene and 400-500 parts of water.

3. The surfactant for increasing the production of low permeability reservoirs according to claim 1, characterized in that: The betaine-type surfactant is prepared by mixing cocamidopropyl betaine and perfluorohexylethylsulfonamidopropylethylcarboxy betaine in a mass ratio of (1-1.5):

1.

4. The surfactant for increasing the production of low permeability reservoirs according to claim 1, characterized in that: The nonionic surfactant is prepared by mixing a fluorocarbon chain nonionic surfactant and ethylenediamine oleate in a mass ratio of (2-3):

1.

5. The surfactant for increasing the production of low permeability reservoirs according to claim 4, characterized in that: The fluorocarbon chain nonionic surfactant is a double short fluorocarbon chain nonionic surfactant.

6. The surfactant for increasing the production of low permeability reservoirs according to claim 1, characterized in that: The modification process of the nano silicon dioxide comprises the following steps: S1: mixing ethanol and 3-mercaptopropyltriethoxysilane in a mass ratio of (4.5-5.5):1; S2: adding nano-silicon dioxide in an amount of 1 / 120-1 / 110 of the mass of the mixed solution to the mixed solution obtained in S1, and stirring the mixture at 25° C. for reaction; S3: centrifuging, washing, recrystallizing and drying the reaction product obtained in S2 in sequence to obtain an intermediate product after drying; S4: dispersing the intermediate product obtained in S3 in dimethylformamide at a mass ratio of 1:(195-205), and performing ultrasonic dispersion; S5: adding an oxygen-containing acid salt having the same mass as the intermediate product in S3 to the product obtained after ultrasonic dispersion in S4, and using a fluorinated surfactant as an initiator to react at 25° C. in an inert gas atmosphere; S6: transferring the product obtained in S5 into cyclohexane, collecting and drying the precipitate to obtain the modified nano-silica.

7. The surfactant for increasing the production of low permeability reservoirs according to claim 6, characterized in that: The solvent used in the recrystallization in S3 is acetonitrile; The oxygen-containing acid salt used in S5 is sodium oleate, and the fluorinated surfactant is sodium perfluorononenyloxybenzenesulfonate; The inert gas is one of nitrogen and helium.

8. The surfactant for increasing the production of low permeability reservoirs according to claim 6, characterized in that: When the stirring reaction is carried out in S2, the stirring speed is 500-600 r / min and the stirring time is 25-30 min; The ultrasonic dispersion time in S4 is 25-30 min, the dispersion power is 1000-1100 W, and the dispersion frequency is 20-25 KHz.

9. A method for preparing a surfactant permeability enhancer for increasing production in low permeability reservoirs according to any one of claims 1 to 8, characterized in that: The steps include: Weigh the following raw materials by weight: 15-30 parts of betaine surfactant, 25-40 parts of nonionic surfactant, 1-5 parts of modified nano-silicon dioxide, 0.5-3 parts of graphene, and 300-600 parts of water; The betaine type surfactant, the nonionic surfactant and 90% of water are uniformly mixed to prepare a surfactant base liquid; The modified nano-silicon dioxide is mixed evenly with the remaining 10% of water to prepare a silicon dioxide base liquid; The graphene and silicon dioxide base liquid are added to the surfactant base liquid under the conditions of ultrasonic dispersion and mechanical stirring to obtain the surfactant penetration enhancer.

10. A use of a surfactant permeability enhancer for increasing the production of a low permeability reservoir as claimed in any one of claims 1 to 8, characterized in that: The surface active permeability enhancer is used as a chemical agent in the production process of low permeability oil reservoirs.

Citation Information

Patent Citations

  • Pressure-reducing and injection-increasing agent for water injection well of low-permeability oilfield, and preparation method and application thereof

    CN106085401A

  • Composite oil displacement system for low-permeability oil reservoir as well as preparation and application methods thereof

    CN110484229A

  • Nano oil displacement agent and preparation method and application thereof

    CN111423866A

  • Tight oil reservoir phase permeability modifying and flooding agent and preparation method thereof

    CN112877051A

  • Nanofluid imbibition agent as well as preparation method and application thereof

    CN113717709A